Prosocial competency-based model of a future teacher - E. I. Eroshenkova; I. S. Shapovalova; E. A. Karabutova; S. V. Anokhina; O. S. Miroshnikova (Образование и наука)
Introduction. Modern general and specific pedagogical trends, mega-trends and challenges in the future education system make it necessary to change the professional training programmes of future teachers, to clarify the competency-based model of a pedagogical university graduate. To achieve pedagogical aims of not only subject, but also of metasubject, educational, social, team-building, helpand project-based character, it is important to form  prosocial competencies of future teachers that allow building “person to person help itinerary”.The aim of the article is to provide theoretical justification and empirical verification of the significant prosocial competencies and individual mindsets of future teachers in the structure of the competency-based model of a pedagogical university graduate according to the future education challenges and priorities.Methodology, methods and techniques. The present research is done in accordance with the methodological principles of integrative, competency-based, culturological and prosocial approaches. An online survey for 582 students of the Institute of Pedagogy of the Belgorod State National Research University was used as a research method. The survey is based on the content-analysis and the content-generalisation of some employment diagnostics for future teachers, as well as the Russian education current regulatory framework.Results. As a result, 36 leading elements in the competency-based model of a future teacher were identified; and the most popular prosocial competencies quartiles (Q1 – “most important”, Q2 – “highly important”, Q3 – “solicited”, Q4 – “most desirable”) were highlighted. Such pedagogical competencies as “subject proficiency” and “humanism, respect for the individual, humanity” are among the leading ones. In the light of priorities within the competency-based model of a future teacher, the flexibility of the specific university training programmes is also revealed. Moreover, the students’ responses allow determining “the ability to develop the other people’s talents and skills” and “the ability to help the other people” as the competencies of the prosocial vector of the competency-based model of a future teacher.The scientific novelty lies in the development of the prosocial competency-based model of a future teacher and in the allocation of 3 clusters of regulatory (stability and adaptability), affective (empathy and communication skills) and stimulating (time management and planning skills) competencies in its structure.The practical significance lies in the use of the materials as starting points for improving the competency-based model of a pedagogical university graduate.